2018
DOI: 10.1016/j.jfluidstructs.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of the vortex-induced vibrations of an untensioned catenary riser with high curvature

Abstract: Measurements of the vortex-induced vibrations of an instrumented catenary model riser with high curvature and very low bending stiffness are presented and discussed. The riser had a diameter of 56mm and a length of 5.36m. It was tensioned only by its own weight and by drag and was tested in a recirculating water channel 2m deep at flow speeds up to 1.4m/s in both directions, i.e. with the upstream anchorage on the floor of the tank and the downstream one at the surface (defined as positive current cases), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Unlike a single-frequency vibration with an RMS amplitude of about 70.7 %, the peak RMS amplitudes in the x and z directions are about 52.4 % and 57.6 % of the corresponding maximum amplitudes, respectively, suggesting the coexistence of multiple modes. This multi-mode characteristic is also confirmed by a variable intersection of vibration envelops and a non-zero node of RMS amplitude along the span (Chaplin et al, 2005;Chaplin and King, 2018;Zhu et al, 2019c). The variation of instantaneous response mode versus a normalized time is plotted in Fig.…”
Section: Resultssupporting
confidence: 55%
“…Unlike a single-frequency vibration with an RMS amplitude of about 70.7 %, the peak RMS amplitudes in the x and z directions are about 52.4 % and 57.6 % of the corresponding maximum amplitudes, respectively, suggesting the coexistence of multiple modes. This multi-mode characteristic is also confirmed by a variable intersection of vibration envelops and a non-zero node of RMS amplitude along the span (Chaplin et al, 2005;Chaplin and King, 2018;Zhu et al, 2019c). The variation of instantaneous response mode versus a normalized time is plotted in Fig.…”
Section: Resultssupporting
confidence: 55%
“…The re-appearance of the vortex shedding was also found in the numerical study of De Vecchi et al (2009), when a concave cylinder was forced to oscillate. Chaplin and King (2018) presented a set of experiments aiming at studying the VIV of a catenary riser with high concave curvature and very low bending stiffness. The authors observed a more complex structural response with respect to springmounted cylinders, accounting for broad-banded displacement spectra.…”
Section: Influence Of the Curvaturementioning
confidence: 99%
“…Contributions of the travelling wave increased as the flow velocity was increased. Some other water tunnel experiments on VIV of a curved flexible cylinder looked into the response of the curved cylinder when the bottom end of the cylinder was completely lying on the floor of the tunnel (Chaplin & King 2018). The frequency content of the spanwise response showed a broad-banded, multi-frequency excitation, where the frequencies of oscillations were found to be lower than those usually observed for a vertical cylinder in flow.…”
Section: Introductionmentioning
confidence: 99%